2012
DOI: 10.1111/j.2044-8295.2012.02128.x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual but sound minds: Mental health indicators in spiritual individuals

Abstract: Previous research has linked certain types of modern spirituality, including New Age and Pagan, with either benign schizotypy or insecure attachment. While the first view emphasizes a positive aspect of spiritual believers' mental health (benign schizotypy), the second view emphasizes a negative aspect, namely the unhealthy emotional compensation associated with an insecure attachment style. This study addresses these two conflicting views by comparing a sample of modern spiritual individuals (N = 114) with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 71 publications
2
21
0
3
Order By: Relevance
“…paradigm described as integral, spiritual teachers, psychologists, health care providers, and theorists have noted that attending to physical, mental, emotional, and spiritual aspects of being in an integrated fashion, particularly in the context of community, may be optimal for achieving psychological well-being (Aurobindo, 1993;Engel, 1977;Farias, Underwood, & Claridge, 2013;Ferrer, 2003;Ginting, Naring, Kwakkenbos, & Becker, 2014;Koenig et al, 2014;Leonard & Murphy, 2005;Schlitz et al, 2005;Short, 2006;Wilber, Patten, Leonard, & Morelli, 2008).…”
mentioning
confidence: 99%
“…paradigm described as integral, spiritual teachers, psychologists, health care providers, and theorists have noted that attending to physical, mental, emotional, and spiritual aspects of being in an integrated fashion, particularly in the context of community, may be optimal for achieving psychological well-being (Aurobindo, 1993;Engel, 1977;Farias, Underwood, & Claridge, 2013;Ferrer, 2003;Ginting, Naring, Kwakkenbos, & Becker, 2014;Koenig et al, 2014;Leonard & Murphy, 2005;Schlitz et al, 2005;Short, 2006;Wilber, Patten, Leonard, & Morelli, 2008).…”
mentioning
confidence: 99%
“…Algumas pessoas podem apresentar experiências e sentimentos fenomenologicamente semelhantes a sintomas psiquiátricos sem, no entanto, apresentar todo o aspecto disfuncional e desorganizado de um transtorno mental (Alminhana et al, 2016;Claridge, 2010;Day, Peters, 1999;Farias, Underwood, Claridge, 2013;Peter et al, 2016;Shofield, Claridge, 2007). Um exemplo são as chamadas "experiências anômalas" (EAs), que se desviam de explicações comumente aceitas da realidade, tais como "experiências fora-do-corpo", "visões e curas espirituais", alegações de "telepatia" ou "mediunismo" (Cardena, Lynn e Krippner, 2004).…”
Section: Introductionunclassified
“…Algumas dessas experiências podem oferecer sentido e promover a saúde mental de muitos indivíduos, quando ressignificadas em contextos religiosos e/ou espirituais (Claridge, 2010;Farias et al, 2013). Por outro lado, algumas vezes tais experiências configuram risco para transtorno mental grave e a Psicologia, especificamente a P s i c o l o g i a d a R e l i g i ã o , p o d e a v a n ç a r n a c o m p r e e n s ã o e n a p o s s i b i l i d a d e d e diferenciação entre indicadores saudáveis e patológicos.…”
Section: Introductionunclassified
“…In contrast, in a much smaller study, Farias et al 7 compared modern spiritual individuals (n=114) with traditional religious believers (n=86) in England. The authors found anxiety, depression, and insecure attachment were not significant predictors of spirituality.…”
mentioning
confidence: 98%